Sequential preovulatory expression of a gonadotropin-releasing hormone-inducible gene, Nr4a3, and its suppressor Anxa5 in the pituitary gland of female rats - Ryota TERASHIMA; Titaree LAOHARATCHATATHANIN; Shiro KURUSU; Mitsumori KAWAMINAMI (The Society for Reproduction and Development, 2021)
Functional relationship between nuclear receptor subfamily 4 group A member 3 (Nr4a3) and annexin A5 (Anxa5), which are two gonadotropin-releasing hormone (GnRH)-inducible genes, has been established while evaluating pituitary gonadotropes in relation to follicle-stimulating hormone beta (Fshb) expression. However, the physiological variations that arise due to the differential expression of these genes in the pituitary gland during rat estrous cycle remain unknown. This study aimed to evaluate the Nr4a3 and Anxa5 mRNA expression during the estrous cycle in rats in comparison with the expression of the gonadotropin subunit genes, luteinizing hormone beta (Lhb) and Fshb. Nr4a3 mRNA expression showed a single peak at 1400 h of proestrus during the 4-d estrous cycle. Anxa5 mRNA level was elevated along with increased Fshb mRNA expression after the decline of Nr4a3 mRNA until 2300 h. Lhb mRNA expression levels were not significantly changed during the estrous cycle. Notably, addition of a GnRH antagonist at 1100 h completely eradicated luteinizing hormone secretion at 1400 h and 1700 h of proestrus, and significantly reduced the Nr4a3 mRNA expression level at both the time points. These results suggest that GnRH is, at least partly, responsible for the increase in pituitary Nr4a3, and that the interaction between NR4A3 and ANXA5 is required to regulate Fshb expression during the preovulatory gonadotropin surge.